2013
DOI: 10.14233/ajchem.2013.f25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanical and Thermal Properties of Polyamide-66/Rubber/Fiber Alloy Composites

Abstract: Generally, a chemical method, such as a new synthesis or the introduction of a functional group and a physical method, which blends two or more polymers at certain ratios to create a desired product, can be used to improve the properties of polymers. Among these physical methods, a polymer blend is used widely because it is relatively simple and the desired properties can be adjusted depending on the polymers used. Polyamide (nylon) with its high crystallization, mechanical properties, thermal stability and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was reported that PA66 has been successfully used to modify epoxy resins to achieve tensile toughness enhancement [26], however there has been limited work related to the use of PA66 for the modification of natural polymers, especially gelatin. Owing to its anti-abrasion resistance, high mechanical strength, light weight, relatively low cost and, very importantly, biological safety [27][28][29][30][31], PA66 can be used as a potential modification material for gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that PA66 has been successfully used to modify epoxy resins to achieve tensile toughness enhancement [26], however there has been limited work related to the use of PA66 for the modification of natural polymers, especially gelatin. Owing to its anti-abrasion resistance, high mechanical strength, light weight, relatively low cost and, very importantly, biological safety [27][28][29][30][31], PA66 can be used as a potential modification material for gelatin.…”
Section: Introductionmentioning
confidence: 99%